Identification of JmjC-domain-containing histone demethylases in sweet cherry reveals PavJMJ12 is required for bud dormancy release - Liu, Ruie; Wang, Li; Usman, Muhammad; Sun, Wanxia; Wang, Qingyuan; Wu, Jian; Nong, Honglin; Zhang, Qijing; Wang, Jiyuan; Zhang, Caixi (International journal of biological macromolecules, 2025)
Global warming poses significant challenges to plant physiology, particularly affecting bud dormancy and fruit yields in perennial fruit trees. JMJ-C domain containing histone demethylases, a family of enzymes that modulate gene expression by removing methyl groups from histone tails, have been the subject of extensive research in model plants like Arabidopsis and tomato. However, their functions in fruit trees, remains largely unexplored. In this study, we identified 16 JMJ histone demethylase enzymes in sweet cherry, which were phylogenetically classified into four distinct classes with molecular weights ranging from 33 kDa to 212 kDa. Phylogenic and expression analysis identified PavJMJ12 as a candidate gene involved in bud dormancy release. Virus-induced gene silencing and transient over-expression of PavJMJ12 demonstrated that PavJMJ12 accelerates bud-dormancy release by activating PavCYP707A2 expression. Furthermore, the H3K27me3 levels reduced dramatically at the region with PavJMJ12 binding site (CTCTGYTY, where Y is C or T) of PavCYP707A2, suggesting that H3K27me3 is involved in regulating PavCYP707A2 expression during bud dormancy release. Collectively, this study provides a comprehensive insight into the functions of PavJMJ histone demethylases and offers a valuable reference for future study in sweet cherry and other fruit trees.